Development Management System of Student Religious Activity through User Centered Design Approach and UTAUT - Suwarno; Syaeful Anas Aklani; Jesselyn (INOVTEK Polbeng - Seri Informatika, 2024)
Project-Based Learning (PBL) is increasingly adopted in educational settings, including MKWU, to foster active engagement and practical skill development. However, managing student religious activities within this framework presents challenges, particularly with manual attendance tracking and inaccurate point calculations. This research aimed to develop a system religious activity for students and mentors, utilizing the User Centered Design (UCD) approach. By employing the Unified Theory of Acceptance and Use of Technology (UTAUT) model, data was collected from 240 respondents through questionnaires. The findings revealed a 99% positive perception of the system regarding its effectiveness, ease of use, peer support, and resource availability. Key features, such as real-time attendance submission and point updates, significantly enhance operational efficiency and accuracy. The study concludes that this UTAUT-based evaluation system effectively meets user needs and boosts engagement in religious studies, marking a shift from traditional manual evaluation methods that often lack real-time feedback and comprehensive metrics